Investigation on the VRB-ESS capacity decay issue - Fan, Fei (2016)
This project investigates the vanadium redox flow battery (VRB) system, in particularly, the capacity decay issue of VRB. Vanadium redox flow battery system is a unique energy storage technology with great potential in grid-scale energy storage due to its decoupled power/energy feature and flexible control strategy. Despite the popularity of VBR system, a series of technical challenges obstruct the widespread implementation. Among these, capacity loss is the key issue limiting the longevity of vanadium flow battery. Capacity loss is mainly caused by the undesired species crossover due to the imperfection of membrane. There are two main parts to this project. The first part is to design a Labview system with graphic interface that allows a user to monitor and control the operation of a vanadium redox flow battery. This part of the project focused on circuit connection, selection of components and LabVIEW graphical program. The second part of this project concentrates on the analysis of the ionic transport mechanisms of capacity decay. Effects of electrolyte concentration flux and species crossover in VRB system are discussed in detail, as well as their relationship with the capacity decay issue. Higher flow rate will always lead to higher concentrate flux and decrease in the species concentration will result in the decrease of charge transfer current density.